Reading Ponoragan Visual Culture on The Visual Development Phenomenon of Dhadhak Merak Reyog Ponorogo - Romzi Akram Al Naufal; Djuli Djatiprambudi; Setyo Yanuartuti (Gondang: Jurnal Seni dan Budaya, 2024)
The dhadhak merak is an iconic mask in Reyog Ponorogo. Over a very long period of time, the dhadhak merak has visually evolved into the form that is often seen today. The visual phenomenon then forms an image of Ponoragan visual culture that is interesting to explore in greater depth. This is what attracts the author's attention to focus on reviewing: 1) The phenomenon of visual development of dhadhak merak over time and 2) Reading Ponoragan visual culture in dhadhak merak. This research is a descriptive qualitative research, with data collection techniques using literature studies and archival documentation. In the process of reading the visual culture of dhadhak merak, the author conducted a review from several aspects, namely: visual structure, function, value, and meaning. The results of this study are 1) The dhadhak merak has undergone seven phases of development starting from its simple dhadhak to the form that is commonly found today. 2) The visual structure, function, historical value, and meaning of the dhadhak merak are constructed on the culture of the people of Ponorogo itself starting from the era of animism-dynamism, Hindu-Buddhism, Islam, to the present era. From that, the Ponoragan culture as a very strong identity marker can be reflected in the dhadhak merak visual culture artifact.